The Influence of the Implementation of Internal Supervision and Good Corporate Governance (GCG) on the Prevention of Fraud at the Bina Administration Foundation - Armansyah; Nurrohmat, Yogi Yogaswara; Kusumah, R. Wedi Rusmawan (CENTRAL ASIA AND THE CAUCASUS, 2022)
The background of this research is that there are still many cases of fraud in various agencies. Fraudulent practice is a danger that can threaten the sustainability of the organization, so preventing fraud is an initial line of defense to protect the organization. The management of the organization has an important role in the process of preventing fraud. The purpose of this study was to determine the effect of internal control and GCG on fraud prevention at the Foundation for Administrative Development (YBA) Bandung. The sampling technique used a saturated sample with a total sample of 42 employees of the Bandung Administration Development Foundation. The research method uses the explanatory method. Data analysis used multiple linear regression. The results show that the implementation of internal control and GCG have an effect on fraud prevention with a large effect of 72.8%.